(untitled) (Nuntius Antiquus, 2015)
This article aims at describing how report and taxis were realised in Herodotus’ Histories. For this purpose, I have organised the most frequent grammatical features of clauses in a small corpus in contrastive sets (systems). With this procedure, I have gathered evidence that both temporal nexuses and report status were realised in Ionic Greek by grammatical features of the clause, which preselected inflectional features of the Finite word and grammatical features of the Subject constituent. These grammatical features could be organised in a systemic network that included systems for determining whether clauses initiate or continue temporal sequences; whether the actor of the initiating clause is the same as the one of the continuant; in case of distinct actors, whether the first is more or less topical than the second; and, finally, whether clauses represent reported locutions or not.